Awareness of the Pandemic H1N1 Influenza global outbreak 2009 among medical students in Karachi, Pakistan - Zubair Ali Khowaja; Muhammad Idrees Soomro; Abdul Khaliq Pirzada; Muhammed Ahmed Yoosuf; Vinod Kumar (Journal of Infection in Developing Countries)
Introduction: This study aimed to assess student awareness of the pandemic pdmH1N1, including the students' attitudes and perceptions about treatment, severity of disease and preventive measures.